Multiobjective Mission Planning for UAV under Uncertain Environment - Wang, Tie Zhu; Wang, Zu Tong; Zhu, Jing Yao; He, Qi Fang (Applied Mechanics and Materials, 2014)
The combat environment of Unmanned Aerial Vehicles (UAVs) is filled with uncertain factors, which is complex and dynamic. This paper is devoted to the UAV mission planning problem under uncertain environment with three optimization objectives, such as flight time, fuel usage and threat imposed by enemy. Based on the uncertainty theory and multiobjective programming method, the UAV uncertain multiobjective mission plaaning model is built and solved.